Bicentennial in Shanghai. The Chilean pavilion and decoration as return to sender - Solís Opazo, José (Revista de Arquitectura, 2015)
Beyond huge architectural, cinematographic and editorial projects celebrating our nation’s bicentennial, 2010 Shanghai’s World Expo Chilean Pavilion shows a paradoxical way to remember the loss of the public issue and the difficulty to define a common history. The origin of these phenomena is based on a particular curatorial strategy of the Pavilion, proposing the domestic interior as representative of the neoliberal Chile. The paradox behind this domestic imaginary, could solely reveal itself in an international exhibition, where the unavoidable banality of our bicentennial celebration can show its real dimension